Joint stakeholders efforts shape tomorrow's digital culture.
Already underway, the digitalisation of culture requires a common vision from all stakeholders in order to truly take off. The SMARTCULTURE project brought together 13 partners from eight European regions to shape future developments in the sector.
Keywords: Digital culture